AYURVEDIC APPROACH TO OSTEOARTHRITIS-A CASE REPORT - N, *Nayana; Misra, Ratnaprava; Kundagol, Mahesh; Chacko, James (International Journal of Ayurveda and Pharma Research, 2016)
Sandhigatavata is a disease in which Vata affects the Joints and cause pain, swelling and pain on Joint movements. It has many causes including Dhathukshaya and injury. The contemporary treatment for this condition includes analgesics and calcium supplements. But it proves to be of little effect. In Ayurvedic science there is a very detailed explanation regarding the medical management of Sandhigatavata which in turn proves to be very effective in its treatment. We hereby report a case of 60yr old female patient complaining of Pain, swelling and restricted movements of Knee, ankle and shoulder joint. She was being diagnosed as a case of osteoarthritis (Sandhigata vata) and was screened on the basis of Kellgrens radiological scale. Treatment was planned as Snehana both internally and externally as Matra vasthi and Abhyanga respectively along with Brihatpanchamoola bala siddha ksheera internally. Visual Analogue Scale for Pain, Swelling score, Womac Scale for assessing daily routine work ability were used to evaluate the efficacy of the treatment. There was a significant improvement in the Visual analogue scale of pain, Range of movements and daily routine work ability. The Quality of life of patient improved significantly by the proper application of internal and external Snehana in this patient. This finding has great relevance in present scenario as a remedy of a very common degenerative disease prevailing in our society.